Continuous lenalidomide and low‐dose dexamethasone in patients with transplant‐ineligible newly diagnosed MM: FIRST trial subanalysis of Canadian/US patients. (13th October 2020) - Belch, Andrew; Bahlis, Nizar; White, Darrell; Cheung, Matthew; Chen, Christine; Shustik, Chaim; Song, Kevin; Tosikyan, Axel; Dispenzieri, Angela; Anderson, Kenneth; Brown, Diane; Robinson, Suzanne; et al.
Abstract: The phase 3 FIRST trial demonstrated significant improvement in progression‐free survival (PFS) and overall survival (OS) with an immune‐stimulatory agent, lenalidomide, in combination with low‐dose dexamethasone until disease progression (Rd continuous) vs melphalan +prednisone + thalidomide (MPT) in transplant‐ineligible patients with newly diagnosed multiple myeloma (NDMM). Rd continuous similarly extended PFS vs fixed‐duration Rd for 18 cycles (Rd18). Outcomes in the Canadian/US subgroup (104 patients per arm) are reported in this analysis. Rd continuous demonstrated a significant improvement in PFS vs MPT (median, 29.3 vs 20.2 months; HR, 0.69 [95% CI, 0.49‐0.97]; p  = 0.03326) and an improvement vs Rd18 (median, 21.9 months). Median OS was 56.9 vs 46.8 months with Rd continuous vs MPT ( p  = 0.15346) and 59.5 months with Rd18. The overall response rate was higher with Rd continuous and Rd18 (78.8% and 79.8%) vs MPT (65.4%). In the 49.0%, 52.9%, and 29.8% of patients with at least very good partial response in the Rd continuous, Rd18, and MPT arms, respectively, the median PFS was 56.0, 30.9, and 40.2 months, respectively. The most common grade 3/4 treatment‐emergent adverse events were neutropenia (28.4%, 30.1%, and 52.0%), anemia (23.5%, 21.4%, and 23.5%), and infections (37.3%, 30.1%, and 24.5%) with Rd continuous, Rd18, and MPT, respectively. These results were consistent with those in the intent‐to‐treat population, confirming the benefit of Rd continuous vs MPT in the Canadian/US subgroup and supporting the role of Rd continuous as a standard of care for transplant‐ineligible patients with NDMM. Abstract : In this Canadian/US subgroup analysis of the FIRST trial, lenalidomide +low‐dose dexamethasone until disease progression (Rd continuous) extended median PFS by 9 months, achieved deeper responses (≈20% increase in ≥VGPR rate), and delayed median TTNT by >14 months vs melphalan +prednisone + thalidomide (MPT). Safety results were generally consistent with the intent‐to‐treat analysis. The results support the role of Rd continuous as a standard of care for transplant‐ineligible patients with NDMM.